Spillover Effect Analysis of Economic Growth Between Regencies in the Pati Residency, Central Java, 1993-2023 (Universitas Muhammadiyah Surakarta, 2025)
Purpose: The purpose of this study is to analyze the influence and causality of inter-regional economic growth and spillover effects in the Pati Residency Area.Methodology: The study employs the Vector Error Correction Model (VECM) to analyze spillover effects and the Granger Causality Test to identify causal relationships between regions.The research uses secondary data on Gross Regional Domestic Product (GRDP) at constant prices for six regencies in the Pati Residency, covering a 31-year period from 1993 to 2023.Results: The findings reveal that inter-regional economic growth relationships are predominantly one-way. There are spillover effects in the form of backwash effects and spread effects. The negative backwash effect was identified as originating from Blora which influenced Rembang, then from Pati and Jepara which influenced Kudus, and from Pati which influenced Jepara. Conversely, a positive spread effect was observed from Kudus spreading to Jepara, and from Rembang which influenced Kudus and Jepara. From these results it can be concluded that in the Pati Residency area the backwash effect occurs more dominantly than the spread effect.Applications/Originality/Value: These results support that the Pati Residency area is in accordance with the Perroux hypothesis which states that economic growth does not occur evenly in all regions, but only regions with certain strengths are able to become growth poles (Kudus and Rembang). The results of this study also show that the circular cumulative causation theory popularized by Myrdal about the emergence of development inequality appears in regions that have a fairly high backwash effect (Blora, Pati, and Jepara).